O uso do sulprostone para esvaziamento médico do conteúdo uterino. - A S Paulo; A C Reis-Morais; M Sá-Correia (Acta Médica Portuguesa, 1996)
The authors describe a one year experience in the Viseu District Hospital Maternity with the use of prostaglandin E2 analog Sulprostone to expel the conceptus. The drug was used in continuous intra-venous administration using a dilution of 1000 mcg of sulprostone in 1000 cc of saline solution. Initially the infusion rate was 0,90 mcg/min (XVIII drops/min) which, was altered to 1,50 mcg/min (XXX drops/min) after a meeting in Espinho in the spring of 1994. The results are presented as success (complete expulsion of uterine contents), partial success and failure. Success (complete and partial) was obtained in 33 cases (62%) and failure in 20 cases (38%). The longer the gestational age the more effective was the drug. Tolerance was very good. We concluded that Sulprostone is an excellent method for medical emptying of the uterus in second and third trimesters.